Efficacy of intravesical gemcitabine instillation compared with intravesical Bacillus Calmette-Guérin instillation for non-muscle invasive bladder cancer - Dong Ha Kim; Taek Sang Kim; Su Hwan Kang; Seong Bin Kim (Kosin Medical Journal)
Background Intravesical Bacillus Calmette-Guérin (BCG) instillation is the most effective treatment for reducing intravesical recurrence in non-muscle invasive bladder cancer (NMIBC). However, due to the recent global shortage of BCG, there is an increasing need for alternative treatments. This study aimed to retrospectively compare the outcomes of patients treated with intravesical gemcitabine instillation and BCG instillation as initial treatment options for NMIBC. Methods Seventy-eight patients with NMIBC who underwent transurethral resection of bladder tumors between January 2022 and September 2023 were reviewed. Of these, 42 patients received intravesical gemcitabine instillation, and 36 patients received BCG instillation. Recurrence-free survival (RFS) was analyzed, along with tumor multiplicity, grade, T stage, size, and bladder storage time after instillation, which could influence RFS. Results The mean follow-up period was 18.7 months for the gemcitabine group and 20.6 months for the BCG group. Recurrence occurred in 46.15% of patients (52.38% in the gemcitabine group and 38.92% in the BCG group). Tumor characteristics, including multiplicity, grade, stage, and size, were not significantly different between the two groups. The mean RFS was 15.92 months in the gemcitabine group and 19.84 months in the BCG group, with no statistically significant difference (p=0.397). However, gemcitabine instillation caused more severe bladder irritation, with shorter bladder storage time. Conclusions Intravesical gemcitabine and BCG instillation yielded comparable RFS outcomes. However, gemcitabine led to more severe bladder irritation, highlighting the need for further studies to optimize its application.